2018
DOI: 10.1098/rsta.2017.0174
|View full text |Cite|
|
Sign up to set email alerts
|

Inter-decadal variability of phytoplankton biomass along the coastal West Antarctic Peninsula

Abstract: The West Antarctic Peninsula (WAP) is a climatically sensitive region where periods of strong warming have caused significant changes in the marine ecosystem and food-web processes. Tight coupling between phytoplankton and higher trophic levels implies that the coastal WAP is a bottom-up controlled system, where changes in phytoplankton dynamics may largely impact other food-web components. Here, we analysed the inter-decadal time series of year-round chlorophyll- (Chl) collected from three stations along the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
69
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(82 citation statements)
references
References 53 publications
6
69
0
7
Order By: Relevance
“…Major penguin breeding colonies around Anvers, Avian, and Charcot Islands are associated with cross‐shelf submarine canyon systems where increased chlorophyll has been recorded throughout the spring/summer season (Prézelin et al ; Ducklow et al ; Oliver et al ; Kavanaugh et al ; Kim et al ). These canyons act as conduits for warm, nutrient‐enriched deep mUCDW to penetrate to the nearshore regions (Prézelin et al ; Martinson et al ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Major penguin breeding colonies around Anvers, Avian, and Charcot Islands are associated with cross‐shelf submarine canyon systems where increased chlorophyll has been recorded throughout the spring/summer season (Prézelin et al ; Ducklow et al ; Oliver et al ; Kavanaugh et al ; Kim et al ). These canyons act as conduits for warm, nutrient‐enriched deep mUCDW to penetrate to the nearshore regions (Prézelin et al ; Martinson et al ).…”
Section: Discussionmentioning
confidence: 99%
“…These biological hotspots have been identified by the presence of major breeding colonies for the Adélie penguins in the WAP (Schofield et al ). Additionally, increased phytoplankton biomass in these regions was evident from satellite observations of ocean color (Kavanaugh et al ) where phytoplankton biomass increases were found between November and March, with peak biomass found in January (Kavanaugh et al ; Kim et al ). The Northernmost site was located at PD near Anvers Island (64.91°S, 64.58°W); a Mid‐WAP site was located at MT near Avian Island (68.03°S, 69.28°W); and the third site was at the Southernmost accessible point along the ice edge off of Charcot Island (CI) (69.11°S, 76.45°W).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interpreting the long-term trends of plankton ecosystems requires an understanding of the link between biological and environmental systems. Because phytoplankton biomass has undergone a significant long-term change since the 1970s (Kim et al 2018), it is necessary to update the previous studies with the recent and longer term environmental and climatic data sets to understand the complexity of phytoplankton biomass variation in the Southern Ocean region.…”
Section: Introductionmentioning
confidence: 99%
“…Bringing complementary datasets together from different international efforts is especially important if we are to deconvolve regional versus local signals in such a highly heterogeneous environment [22]. Drawing in other disciplines that will mesh with marine science such as glaciology, atmospheric science and palaeoclimate will also be critical, as will engagement with other organizations and with policy, industry, education and with the public via 'citizen science', through dialogues with cruise ship operators, and development of apps and approachable literature.…”
mentioning
confidence: 99%